FOOD SECURITY AND LAND USE CHANGE: A COLLABORATIVE WORK BETWEEN WOMEN’S FARMER GROUPS AND THE GOVERNMENT OF RAJABASA JAYA URBAN COMMUNITY IN BANDAR LAMPUNG - Arizka Warganegara; Azis Ahmad Azis; Afriliah Nur Fadilah (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
The change in land use from agricultural to non-productive land has resulted in a serious threat to local food security, particularly in urban areas like the city of Bandar Lampung. This study aims to analyse the impact of land use change on local food security and to explore the collaborative work between the Women Farmers Group and the village government from the perspective of a good local governance framework. This research applies a descriptive qualitative approach, with data collection methods consisting of in-depth interviews, participatory observation, and document analysis, and the research location is in the Rajabasa Jaya urban community, an area under significant threat from land use change and the potential decrease in the women’s community’s active engagement in food production as a result. Preliminary findings have shown that land use change has led to a local decline in food availability and an increasing dependency on external food supplies. Furthermore, the Women Farmers Group has continued to actively utilize home gardens and produce food with support from the village government. This collaborative work reflects that good practice in local governance could strengthen community food security, although challenges would remain in terms of increasing production capacity and the sustainability of the programme. This study endeavours to contribute to the development of a participatory governance model and to create policy recommendations for strengthening the sustainability of food supply and production at the village level.